DETERMINANTS OF BANK PROFITABILITY IN INDONESIA BASED ON COMMERCIAL BANK BUSINESS ACTIVITIES (BUKU) - Marlina, Reni (JBFEM, 2022)
This study aims to determine the determinants of the profitability of banks in Indonesia based on the Commercial Group Business Banks (BUKU). Descriptive and verification methods used on secondary form bank that go public in Indonesian Stock Exchange. The dependent variable is Return on Assets (ROA) and the independent variables are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operational Expense of Operating Income (OEOI) and Net Interest Margin (NIM). The results showed that Â in BUKU 2, OEOI has a significant negative effect on ROA while CAR and LDR have a negative and insignificant effect on ROA and NIM has a positive and insignificant effect on ROA. In BUKU 3, it showed that CAR has a significant positive effect on ROA, for LDR and NIM has a positive and insignificant effect on ROA while for OEOI it has a negative and insignificant effect on ROA. In BUKU 4, Â CAR, LDR and ROA have negative and insignificant effect on ROA and NIM have a significant positive effect on ROA. Simultaneously, CAR, LDR, OEOI and NIM have an effect on ROA for Bank BUKU 2,3 and 4.